A model for faculty engagement in distributed medical education: Crafting a paddle (Canadian Medical Education Journal, 2018)
Distributed medical education initiatives are now a key component of all Canadian medical schools.  The success of these initiatives requires engaged community-based faculty who are able to successfully balance both their clinical and educational responsibilities. Present understanding of faculty engagement within distributed medical education is limited. Faculty engagement is a complex and multifaceted construct that includes a reciprocal relationship between a Faculty of Medicine and their faculty. Clarification of both the extrinsic and intrinsic motivators of distributed faculty provide opportunities for Faculties of Medicine to more fully engage their faculty and sustain distributed medical education programs.